2018
DOI: 10.1186/s12936-018-2590-0
|View full text |Cite
|
Sign up to set email alerts
|

Brain swelling is independent of peripheral plasma cytokine levels in Malawian children with cerebral malaria

Abstract: BackgroundCerebral malaria (CM) is often fatal, and severe brain swelling is a predictor of CM-related mortality. CM is characterized by elevated circulating pro-inflammatory cytokines TNF and IFN-γ and anti-inflammatory cytokine IL-10, however whether cytokine levels correlate with brain swelling severity is unknown. This study therefore was conducted to investigate the relationship between cytokine levels and brain swelling severity in children presenting with CM.MethodsA total of 195 Malawian children prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 37 publications
0
18
1
Order By: Relevance
“…Some studies reported that IFNg, TNF, IL-1b, IL-4, IL-6, IL-8, IL-10, IL12p70, and/or CXCL10 were elevated in children with cerebral malaria compared to those with uncomplicated malaria (134)(135)(136), while others reported no difference in cytokine levels between the groups (137). The degree of brain swelling was independent of plasma levels of IL-1b, IL-6, IL-8, and IL-10 in children with cerebral malaria, while IL-12 and TNF were elevated in patients with more severe edema (138).…”
Section: Inflammatory Mediators In Cerebral Malariamentioning
confidence: 89%
“…Some studies reported that IFNg, TNF, IL-1b, IL-4, IL-6, IL-8, IL-10, IL12p70, and/or CXCL10 were elevated in children with cerebral malaria compared to those with uncomplicated malaria (134)(135)(136), while others reported no difference in cytokine levels between the groups (137). The degree of brain swelling was independent of plasma levels of IL-1b, IL-6, IL-8, and IL-10 in children with cerebral malaria, while IL-12 and TNF were elevated in patients with more severe edema (138).…”
Section: Inflammatory Mediators In Cerebral Malariamentioning
confidence: 89%
“…It may suggest that systemic low-grade inflammation in patients with mTBI reflects disease severity not obviously linked to neuroradiological findings, a fact reported in other diseases such as febrile status epilepticus and brain swelling in cerebral malaria. 39,40 Likewise, more severe injury indicated by lower GCS score was negatively associated with eotaxin and MIP-1b. Although GCS score has been shown to be an important predictor of morbidity in severe TBI, 41 it has shown relatively poor prognostic utility in mTBI, 42 and to our knowledge, its relation with inflammatory markers has not been investigated.…”
Section: Associations Between Increased Cytokine Plasma Levels and Inmentioning
confidence: 93%
“…For example, therapeutic sphingosine-1-phosphate (S1P) blocking agents, such as FTY720 decreased lymphocyte trafficking into the brain and lowered peripheral IFNγ levels [74]. Not all studies have found a relation between peripheral cytokines and cerebral oedema in CM [75].…”
Section: Neuropathogenesis Of Cerebral Malariamentioning
confidence: 99%